An overview of plasticity of Si crystals governed by dislocation motion. (October 2015) - Yonenaga, Ichiro
Highlights: Mechanical strengths of Si crystals were reviewed. The brittle-to-ductile transition was discussed in terms of sample size and atmospheric conditions. Dislocation motion in a shuffle- and glide-set core structure was considered in relation with crystal strength. Abstract: Several aspects of deformation of silicon from room temperature to the melting temperature, such as the deformation mode of brittle-to-ductile transition, small or conventional sample size and deformation atmosphere of ambient or confining pressure were comprehensively overviewed. Dislocation motion was then examined in terms of the core structure of shuffle- or glide-set dislocations and high or low applied stress. At elevated temperatures plastic deformation is governed by the collective motion of glide-set dislocations. At low temperatures generation of shuffle-set dislocations may be favorable under the application of high stress.